Karakteristik Radiologi Foto Toraks Terhadap Penderita Pneumonia Anak di Rumah Sakit Royal Prima Ayahanda Medan - Sulistiawati, Sulistiawati; Pulungan, Ica Yulianti; Nadapdap, Marshall Jeremia (Syntax Corporation, 2025)
Pneumonia is as an acute respiratory infection that affects lung tisuue and stands as one of the primary causes of mortality among children worldwide.. According to the World Health Organization (WHO, 2022), pneumonia is caused by infectious agents such as Streptococcus pneumoniae, Haemophilus influenzae type b (Hib), and Respiratory Syncytial Virus (RSV). UNICEF (2024) reports that more than 700,000 children under the age of five die annually due to pneumonia. Radiological chest X-ray examination plays an essential role in detecting pulmonary abnormalities such as infiltrates, consolidation, and bronchopneumonia (Az et al., 2021). It also assists in distinguishing between bacterial and viral pneumonia (Aprilia et al., 2024). Objective to determine the radiological characteristics of chest X-ray findings in pediatric patients with pneumonia at Royal Prima Ayahanda Hospital Medan. Methods this research employed a descriptive retrospective study design using a cross sectional approach. Secondary data were collected from the medical records of pediatric pneumonia patients at Royal Prima Ayahanda Hospital, Medan, during 2022–2023. A total of 57 pediatric patients who met the inclusion and exclusion criteria were included. Data were analyzed univariately and presented in frequency and percentage distributions based on variables such as age, gender, infiltrate, and consolidation findings. The results showed that the most common age group was 0–1 years (42.1%), with females predominating (61.4%). Chest X-ray examination revealed that 75.4% of patients had abnormal radiological findings. The most frequent feature was pulmonary infiltrate (77.2%), while consolidation was found in 21.1% of patients. Conclusion most pediatric pneumonia patients demonstrated abnormal radiological chest X-ray findings, predominantly alveolar infiltrates. Chest X-ray examination remains an important diagnostic tool in assessing lung involvement and determining the severity of pneumonia in children.